3D-printed in-line and out-of-plane layers with stimuli-responsive intelligence. (December 2022) - Ravichandran, Dharneedar; Kakarla, Mounika; Xu, Weiheng; Jambhulkar, Sayli; Zhu, Yuxiang; Bawareth, Mohammed; Fonseca, Nathan; Patil, Dhanush; Song, Kenan
Abstract: Smart materials and structures with shape memory properties have recently gained attention due to their unique ability to remember their original shape, dimensional flexibility, structural programmability, and multi-material compatibilities. They have found applications in morphing structures, heat storage, flexible electronics, soft/micro-robotics, metamaterials, biomedical scaffolds, and space missions. Most applications of these systems require multifunctionality with high precision controls over multi-materials. However, most current manufacturing cannot process disparate materials without generating phase separation or structural instabilities. This research presents a new 3D printing process via the Multiphase Direct Ink Writing (MDIW) mechanism to produce in-line and out-of-plane microlayers. The selective deposition of polyether-thermoplastic polyurethane (TPU)/polycaprolactone (PCL) and polyester-TPU/iron oxide (Fe3 O4 ) is investigated for thermal and magnetic dual stimuli-responsiveness. During the MDIW manufacturing, specific sublayers within each printing line for optimized domain size are produced with the stacking of the layers along the z-axis to investigate their influences on the stimuli-responsiveness. The mechanical, thermal, and thermomechanical characterizations can reveal the time-temperature-dimension relationships in different media (i.e., air and water) showing a precisely controlled actuation phenomenon and shedding light on their broad applications in defense, energy, health, and sustainability. Graphical abstract: Image 1